Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Adaptive Software Development: A Collaborative Approach to Managing Complex Systems - Highsmith, Jim (Dorset House Publishing, 2000)
In today's turbulent e-business world, software project teams that survive and thrive won't be those that continue their traditions of optimization, efficiency, and control, but those that exhibit adaptability, speed, and collaboration. Adaptive Software Development is targeted at software teams where competition creates extreme pressure on the delivery process. Four goals of the book are * to support an adaptive culture in which change and uncertainty are assumed to be the natural state * to introduce frameworks to guide the iterative process of managing change * to institute collaboration, the interaction of people on interpersonal, cultural, and structural levels * to add rigor and discipline to the RAD approach, making it scalable to the uncertainty and complexity of real-world undertakings. This innovative text, grounded in the science of complex adaptive systems theory, offers a practical, realistic approach to managing the high-speed, high-change projects characteristic of our highly uncertain economy.

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (IDS, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments―now updated with new techniques for larger projectsToday, the pace of project management moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromising value, quality, or business discipline. In Agile Project Management, Second Edition, renowned agile pioneer Jim Highsmith thoroughly updates his classic guide to APM, extending and refining it to support even the largest projects and organizations. Writing for project leaders, managers, and executives at all levels, Highsmith integrates the best project management, product management, and software development practices into an overall framework designed to support unprecedented speed and mobility. The many topics added in this new edition include incorporating agile values, scaling agile projects, release planning, portfolio governance, and enhancing organizational agility. Project and business leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, quality, and constraints. This edition’s coverage includes: Understanding the agile revolution’s impact on product development Recognizing when agile methods will work in project management, and when they won’t Setting realistic business objectives for Agile Project Management Promoting agile values and principles across the organizationUtilizing a proven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five stages of the agile project: Envision, Speculate, Explore, Adapt, and CloseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for executives and management The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

A Refresher on Discovery-Driven Planning - Gallo, Amy (Harvard Business Review)

Discovery-Driven Planning - McGrath, Rita; MacMillan, Ian (Harvard Business Review)

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (USAID LEARN, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)